Penetrating injury to the maxilla and skull base resulting in the mount fuji sign of tension pneumocephalus and ipsilateral vision loss - Reddy Ravikanth; Ashwin Chandrasekhar; Anegh Pavithran; Sivakumar Kandasamy; John Joshy (Wolters Kluwer Medknow Publications, 2019)
Pneumocephalus is defined as the presence of intracranial air seen most commonly secondary to a traumatic head injury. Tension pneumocephalus is often termed in radiology as the Mount Fuji sign due to a perceived similarity with the iconic mountain peak in Japan. We present the case of a 62-year-old gentleman who presented to the emergency department following a penetrating injury to the right maxilla and skull base which resulted in acute-onset ipsilateral vision loss due to direct traumatic injury to the optic nerve by the fractured bone fragments encountered in the optic canal.